2016
DOI: 10.1080/14328917.2015.1131416
|View full text |Cite
|
Sign up to set email alerts
|

Sodium dodecyl sulfate (SDS) as a filler treatment: effects on mechanical, morphological and swelling properties of poly (vinyl chloride) (PVC)/epoxidized natural rubber (ENR)/kenaf core powder composites

Abstract: The effects of SDS treatment on properties of PVC/ENR/kenaf core powder composites were studied. Four different loadings of kenaf core powder (5, 10, 15 and 20 phr) were used. Samples were prepared using a Haake Polydrive with the temperature of 140 °C and rotor speed of 50 rpm, with the processing time of 8 min. Processing torque and stabilization torque during the compounding process were recorded. Tensile properties indicated that the tensile strength and elongation at break of the composites exhibited an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A clear evidence for the weak interfacial area between SPEEK matrix and ENR-50 was observed with an increasing of ENR-50 loading [9,10]. Fig 1 (c and d) exposed that the particle size of ENR-50 decrease while the domain size increase with the increasing of ENR-50 content from 1.5 wt% to 2.5 wt%.…”
Section: Resultsmentioning
confidence: 84%
“…A clear evidence for the weak interfacial area between SPEEK matrix and ENR-50 was observed with an increasing of ENR-50 loading [9,10]. Fig 1 (c and d) exposed that the particle size of ENR-50 decrease while the domain size increase with the increasing of ENR-50 content from 1.5 wt% to 2.5 wt%.…”
Section: Resultsmentioning
confidence: 84%
“…The work showed that the tensile properties and thermal stability increased due to improved fiber/matrix interface. Other works have also reported on the favorable effect of SDS on various composite characteristics 46,47 …”
Section: Introductionmentioning
confidence: 93%
“…Other works have also reported on the favorable effect of SDS on various composite characteristics. 46,47 Although alkali treatment is a widely used technique to modify natural fibers in order to improve fiber/matrix interface of their composites, there has not been a study that investigates the effect of SDS on the efficacy of alkali treatment of hemp fibers. In this work, it was proposed that adding SDS would improve the efficiency of hemp fiber alkali treatment by removing the waxy layer on the fiber surface and facilitating the access of hydroxyl ions into the fiber structure, leading to more efficient removal of fiber ingredients like pectin, lignin, and hemicelluloses.…”
Section: Introductionmentioning
confidence: 99%